2023
DOI: 10.3390/biology12020263
|View full text |Cite
|
Sign up to set email alerts
|

Plastid Phylogenomic Insights into the Inter-Tribal Relationships of Plantaginaceae

Abstract: Plantaginaceae, consisting of 12 tribes, is a diverse, cosmopolitan family. To date, the inter-tribal relationships of this family have been unresolved, and the plastome structure and composition within Plantaginaceae have seldom been comprehensively investigated. In this study, we compared the plastomes from 41 Plantaginaceae species (including 6 newly sequenced samples and 35 publicly representative species) representing 11 tribes. To clarify the inter-tribal relationships of Plantaginaceae, we inferred phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 91%